Applied drama : the gift of theatre - Nicholson, Helen, 1958- (Houndmills, Basingstoke, Hampshire ; New York, NY : Palgrave Macmillan, 2014)
"Applied Drama offers an insight into theatre-making that takes place in communities across the world. It considers the role of artists who work in challenging settings, including prisons, schools, hostels for the homeless, care homes for the elderly and on the street. In this updated second edition, Helen Nicholson provides vivid new examples of practice, and addresses twenty-first century concerns about the environments in which applied theatre takes place. Ideal for students and practitioners, this lively study poses critical questions about the aesthetics and ethics of applied theatre. It invites debate about the social role of theatre, and explores how interventionist theatre might maintain its radicalism in an increasingly globalized world"--
Machine generated contents note: -- Acknowledgements -- General Editors' Preface -- 1. An Introduction to Applied Drama, Theatre and Performance -- PART I: PARTICIPATION AND PRAXIS -- 2. The Practice of Citizenship -- 3. Pedagogies, Praxis and Performance -- PART II: NARRATIVES AND NARRATIVITY -- 4. Narrative and the Gift of Storytelling -- 5. Community Narratives: Space, Place and Time -- PART III: CREATIVITY AND SOCIAL JUSTICE -- 6. Creativity and Social Intervention -- 7. Human Rights in Performance -- PART IV: EPILOGUE -- 8. The Gift of Theatre -- Notes -- Bibliography -- Index.
Includes bibliographical references (pages 193-205) and index.
Keywords: Theater and society; PERFORMING ARTS / Theater / General; PERFORMING ARTS / Theater / Direction & Production; PERFORMING ARTS / Theater / History & Criticism